2019
DOI: 10.1002/ejlt.201800339
|View full text |Cite
|
Sign up to set email alerts
|

1H LF‐NMR Energy Relaxation Time Characterization of the Chemical and Morphological Structure of PUFA‐Rich Linseed Oil During Oxidation With and Without Antioxidants

Abstract: A major stability issue of food and other products containing lipids is their susceptibility to oxidation and the efficacy of endogenous or exogenous antioxidants that are sensitive to internal morphological and chemical structures which are difficult to characterize with current analytical methods. This work develops signal reconstruction of 1H LF‐NMR spin‐lattice (T1) and spin‐spin (T2) energy relaxation times into 2D T2 versus T1 peak graphs of the internal chemical and morphological arrangements within lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…The present study was carried out as a follow‐up of our previous publications presenting the 1 H LF‐NMR 2D T 1 –T 2 graphical maps for butter, rapeseed oil, soybean oil, and linseed oil (Resende et al, 2019a, b). These articles showed that the composition of the saturated/unsaturated fatty acids affects the triacylglyceride (TAG) oil's chemical and morphological energy relaxation time domains, which could be correlated to its oxidative propensity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study was carried out as a follow‐up of our previous publications presenting the 1 H LF‐NMR 2D T 1 –T 2 graphical maps for butter, rapeseed oil, soybean oil, and linseed oil (Resende et al, 2019a, b). These articles showed that the composition of the saturated/unsaturated fatty acids affects the triacylglyceride (TAG) oil's chemical and morphological energy relaxation time domains, which could be correlated to its oxidative propensity.…”
Section: Resultsmentioning
confidence: 99%
“…Autoxidation experimental design was based on previous studies (Berman et al, 2016; Meiri et al, 2015; Resende et al, 2019a, b; Wiesman et al, 2018). Briefly, six samples of 250 mL of linseed oil in 500 mL beakers were heated on a hot plate at different temperatures (25, 40, 60, 80, 100, and 120 °C).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations